Findings of an Empirical Study on the Image of Geography at School from the Perspective of Students at Secondary Level (in North Rhine-Westfalia) - Miener, Kim Pascal (Journal of Geography Education, 2017)
The images of school subjects are of importance not only from an educational policy perspective. They also have an influence on the general attitude of pupils towards their subjects. This means that image is one of many predictors for the success of geographical education in the classroom. That concept of image can be operationalised and accessible by surveying the attitudes of pupils towards their subjects. What image do pupils have of geography as a school subject? Which factors influence those images? Can images be influenced externally? Which role do teachers have in context of image development? These questions are examined in a hypothesis testing quantitative study on pupils' attitudes within secondary level in North Rhine-Westfalia. For this purpose, a quantitative measuring instrument had to be designed, which aggregates the partial findings about subject attitudes of previous studies and brings them into line with the present circumstances. The statistical analysis and interpretations show that the overall image is positive. There are weaknesses and improvements needed in terms of motivation for geographical topics considering the subject. In contrast, the relevance, scientific character and level of difficulty get positive evaluations by the pupils. Furthermore, the pupils name orientation skills as a distinctive feature of the subject, although there is still great need for further research on this facet of pupils' image of geography. The analysis of influencing factors shows that age, gender and school type don't have great impact on the context of image. In contrast to this the didactical and methodical planning are the influencing factors with the greatest effect on the image. In addition, the teachers’ personality and pupils' overall attitude towards school have great effects on this image. The pupils’ overall geographical interest outside of school is another effective factor in terms of personal variables. All in all, it appears that pupils' subject image can be overly influenced externally especially by teaching methods. This allows teachers to be an active part in the concept of image development.
Keywords: geographical education, image, attitude, learners preconditions